Purulent pericarditis as a complication of pneumonia in an infant. Clinical case report - Diego Alejandro Lozano Espinosa; Olga Yamile Castiblanco Rubio; Juan Carlos Bustos Acosta; Roy Sanguino Lobo; Germán Camacho Moreno; Edgar Hernando Rojas Soto (Case Reports, 2018)
Introduction: Purulent pericarditis is an inflammatory process in the pericardium caused by bacterial infection. If experienced during childhood and with untimely diagnosis, it has a high mortality rate.